Risk of heart failure depending on the state of renal filtration function in patients with uncomplicated hypertension - A. I. Chernyavina; N. A. Koziolova (Российский кардиологический журнал)
Aim. To assess the risk of heart failure (HF) depending on the state of renal filtration function in patients with uncomplicated hypertension (HTN) without kidney dysfunction.Material and methods. This cross-sectional screening clinical trial consecutively included 176 outpatients with uncomplicated HTN and without chronic kidney disease (CKD). To assess the HF risk, the blood concentration of N-terminal pro-brain natriuretic peptide (NT-proBNP) was determined. To assess the renal filtration function, the blood serum concentration of creatinine and cystatin C was determined, followed by glomerular filtration rate (GFR) estimation using the CKDEPI equation with both parameters. Echocardiography was performed to assess the cardiac structural and functional state.Results. Correlation analysis revealed a moderate direct relationship between NT-proBNP and blood cystatin C concentration (r=0,370; p<0,005), as well as a moderate inverse relationship with GFR (CKD-EPIcre) and GFR (CKD-EPIcys) (r= -0,321; p<0,05 and r=-0,360; p<0,005, respectively). ROC curve for all available values of blood cystatin C revealed the most optimal cut-off threshold of 1016 ng/ml (AUC=0,726, p<0,001), which ensures the sensitivity of 72,2% (p<0,001) and specificity of 62,0% (p<0,001). ROC curve for all available GFR values (CKD-EPIcys) revealed a cut-off threshold of 74 ml/min/1,73 m2 (AUC=0,702, p=0,002) with a sensitivity and specificity of 55,6% and 74,7%, respectively (p=0,001 and p=0,001, respectively). Taking into account the cut-off points for cystatin C and GFRcys, the first group consisted of 73 (41,48%) patients with cystatin C ≥1016 ng/ml and GFR (CKD-EPIcys) ≤74 ml/min/1,73 m2, while the second one — 103 (58,52%) patients with cystatin C <1016 pg/ml and GFR (CKDEPIcys) >74 ml/min/1,73 m2. The presence of impaired glucose tolerance, left ventricular diastolic dysfunction (LV DD), LV hypertrophy and left atrial enlargement leads to an additional increase in HF risk in patients with uncomplicated HNT without CKD.Conclusion. The ROC analysis showed that cystatin C and cystatin C-based GFR (CKD-EPIcys) can be used as markers of HF risk in patients with uncomplicated HTN without CKD. With an increase in cystatin C ≥1016 ng/ml, the relative risk of HF is 2,99, while with a decrease in GFR (CKD-EPIcys) ≤74 ml/min/1,73 m2 — 1,26. The presence of impaired glucose tolerance, LV DD, LV hypertrophy and left atrial enlargement in patients with uncomplicated HTN without CKD with a cystatin C increase ≥1016 ng/ml and a decrease in GFR (CKD-EPIcys) ≤74 ml/min/1,73 m2 and below further increases the risk of developing CHF.